Assessment of Racial Disparities in Aspirin Prophylaxis for Preeclampsia Prevention - Ragunanthan, Nina W.; Lamb, Jordan; Hauspurg, Alisse; Beck, Stacy (American Journal of Perinatology, 2022)
Objective Low-dose aspirin is recommended for preeclampsia prevention among women with high-risk conditions, including chronic hypertension. Black women have higher rates of hypertensive disorders of pregnancy, and whether this is related to disparities in aspirin prophylaxis is unknown. We investigated the relationship between race and counseling/prescription and uptake of aspirin among a cohort of women with chronic hypertension.Study Design This is a single-institution, retrospective cohort study of women with chronic hypertension who delivered between 2016 and 2018. Medical record review was performed to assess counseling/prescription of aspirin prophylaxis and self-reported uptake. Self-reported uptake was determined by mention in the provider's notes or by inclusion in the medication reconciliation system. Demographic and obstetric outcome data were compared by self-reported race (Black vs. all other races) in univariate analysis. Multivariable logistic regression analysis was performed to evaluate the association between race and aspirin adherence.Results We included 872 women: 361 (41.4%) Black women and 511 (58.6%) white or other race women. Overall, 567 (65.0%) women were counseled and/or given a prescription for aspirin, and 411 (72.4%) of those women reported uptake. Black women were equally likely to be counseled and/or prescribed aspirin compared with all other races (67.3 vs. 63.4%; p = 0.7). However, Black women were less likely to report uptake of aspirin (63.8 vs. 79.0%; p < 0.001). After adjustment for total prenatal visits and tobacco use, Black race was associated with an adjusted odds ratio of 0.53 (95% confidence interval: 0.36–0.78) for uptake of aspirin.Conclusion In our cohort, recommendation for aspirin prophylaxis was suboptimal in all groups, reaching only 65% of eligible women. Black women were equally likely as women of other races to receive counseling about aspirin, but rates of uptake were lower. Our findings suggest that counseling and prescription of aspirin alone in high-risk Black women are not sufficient for utilization of this intervention.Key Points
Keywords: preeclampsia; aspirin; racial disparities; medication uptake